Respuesta :

leena

Hello! :)

[tex]\large\boxed{\frac{dy}{dx} = 3^{(2x^{2} - 1)} (4x^{2}ln3 + 1)}[/tex]

Use the Product Rule to solve for the derivative:

[tex]\frac{dy}{dx}= f(x) * g'(x) + g(x) * f'(x)[/tex]

We can divide the expression into two different functions:

[tex]f(x) = x\\\\g(x) = 3^{2x^{2} -1}[/tex]

Use the Product Rule equation and the following rules to solve for the derivative:

Derivative of an exponential function with base other than e:

[tex]\frac{dy}{dx} a^{u} = a^{u} * u' * lna[/tex]

Power rule:

[tex]\frac{dy}{dx} x^{n} = nx^{(n-1)}[/tex]

Find the derivatives using the power rule and derivative of an exponential function. Plug these into the product rule equation:

[tex]\frac{dy}{dx} = x(3^{(2x^{2} -1)} * 4x* ln3) + (1)3^{(2x^{2} - 1)}[/tex]

Simplify by factoring out a common factor:  [tex]3^{(2x^{2} - 1)}[/tex]

[tex]\frac{dy}{dx} = 3^{(2x^{2} - 1)}( x* 4x * ln3) + (1)[/tex]

Simplify further:

[tex]\frac{dy}{dx} = 3^{(2x^{2} - 1)} (4x^{2}ln3 + 1)[/tex]

This is the final derivative.

Wolfyy

Answer:

[tex]3^{2x^2-1}+4ln(3)*3^{2x^2-1}x^2[/tex]

Step-by-step explanation:

[tex]x3^{(2x^2-1)}[/tex]

~Apply product rules

[tex]\frac{d}{dx}(x)3^{2x^2-1}+\frac{d}{dx}(3x^{2x^2-1})x\\\frac{d}{dx}=1\\(3^{2x^2-1})=4ln(3)*3x^{2x^2-1}x\\1*3^{2x^2-1}+4ln(3)*3^{2x^2-1}xx[/tex]

~Simplify

[tex]3^{2x^2-1}+4ln(3)*3^{2x^2-1}x^2[/tex]

Best of Luck!

ACCESS MORE